Diversity of mantis (Insecta : Mantodea) in Sabah, Malaysia - Khairui Nizam Yakob (2012)
This study was carried out to determine the accumulation capacity of selected mosses as active bioindicators for atmospheric heavy metals (Cd, Cr, Cu, Pb, and Zn) on Mount Kinabalu, Sabah. Ten local moss species were selected, namely Brachythecium plumosum, Breutelia arundinifolia, Hypnodendron dendroides, Leucobryum Javense, leucobryum sumatranum, Sphagnum cuspidatum, Sphagnum sericeum, Spinaens reinwardtii, Trismegistia calderensls, and Trismegistia panduriformis. The mosses were collected within the Kinabalu Park and acclimatised in a temperature-controlled room (12-17 °C) for about one week. Subsequently, they were transplanted using nylon moss bags at nine monitoring sites for three months and periodically monitored after 30, 60, and 90 days of exposure. The monitoring sites were divided into three different zones, namely roadside, in park, and on mountain. The concentrations of heavy metals in the desiccated apicat shoots of mosses were determined by flame atomic absorption spectrophotometry (F-AAS). The chlorophyll contents of the mosses were determined by ultraviolet (UV) spectrophotometer. The results revealed that Pb element was the highest heavy metal poflutant in the study area. The metal concentration in the moss samples significantly increased with the duration of exposure and was higher at the roadside. The level of heavy metal pollutants were arranged as Pb > Zn > Cr > Cd > Cu. In general, the accumulated metals were significantly correlated (at p < 0.01) with the nine monitoring sites and four exposure periods. However, it has no significant correlation with the chlorophyll contents in the mosses, which suggests that other condition have a greater influence on the chlorophyll concentration. Breutelia arundinifolia and Trismegistia panduriformis were the best bioindicators, among the ten selected species, for atmospheric heavy metal pollutants. In conclusion, local mosses have potential as bioindicators of heavy metals in tropical highlands and could be used in long term monitoring measures.